2021
DOI: 10.6007/ijarbss/v11-i8/10581
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Macroeconomic Factors and The Performance of Stock Market in Malaysia: The Case of Malaysia Industrial Product and Services Sector

Abstract: For years, researchers have been studying the factors that influence stock market performance. Typically, it concentrates on Malaysia's macroeconomic conditions. The goal of this study is to close the gap by examining the elements that influence the stock market's production in Malaysia. More precisely, it includes real exchange rate, money supply, inflation rate inflation rate and US stock market in measuring their relationships with the performance of the Malaysian stock market price. This analysis attempts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This availability of extra money in an economy in the form of broad money gives a boost to the service sector. This outcome is backed by the past study of Ya'acob et al. (2021), as they find that money supply has a positive effect on service sector growth.…”
Section: Long Run Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…This availability of extra money in an economy in the form of broad money gives a boost to the service sector. This outcome is backed by the past study of Ya'acob et al. (2021), as they find that money supply has a positive effect on service sector growth.…”
Section: Long Run Resultsmentioning
confidence: 81%
“…This availability of extra money in an economy in the form of broad money gives a boost to the service sector. This outcome is backed by the past study of Ya'acob et al (2021), as they find that money supply has a positive effect on service sector growth. Since these interrelationships between the variables indicate that there may be multicollinearity between the selected variables.…”
Section: Long Run Resultsmentioning
confidence: 81%
“…Not necessarily, all the economic factors play an important role in stock market performance. A recent study by Ya'acob et al. (2021) revealed that only three variables were significant, while inflation did not seem to have affected the stock market.…”
Section: Existing Literaturementioning
confidence: 92%